Pain Acceptance in Adolescents: Development of a Short Form of the CPAQ-A. (28th November 2018) - Gauntlett-Gilbert, Jeremy; Alamire, Batool; Duggan, Geoffrey B
Abstract: Objective: Acceptance of pain is a predictor of pain-related disability and treatment outcome in adolescents with pain. This variable has been previously measured using the Chronic Pain Acceptance Questionnaire for Adolescents (CPAQ-A, McCracken, Gauntlett-Gilbert, & Eccleston, European Journal of Pain, 14, 316–320, 2010). We set out to create a short, eight-item, form of this instrument that retained its factor structure and clinical utility. Methods: We used data collected from two independent samples of adolescents attending residential treatment for disabling chronic pain ( N  = 187 and N  = 159). Both groups completed the 20-item CPAQ-A and indices of functioning and distress. We carried out item reduction and confirmatory factor analysis (CFA) on the first sample, repeating this on the second sample and examining the new scale's correlations with clinically relevant variables. Results: An eight-item scale was created with four items assigned to each established factor (Pain Willingness and Activity Engagement). CFA confirmed this factor structure and it replicated in Sample 2. The new scale (the CPAQ-A8) was sensitive to treatment and correlated as well with clinically important variables as its full-length version. Some items in the new scale differed from the adult CPAQ-8. Conclusions: Measures of pain acceptance have been previously developed and validated in pediatric and adult samples. This study showed that pain acceptance can be indexed by a brief, yet factorially valid, short form of the CPAQ-A that uses fewer than 50% of the items of the full-length scale and has demonstrated acceptable validity and sensitivity-to-treatment.